Histopathological and immunophenotypical characterization of canine multicentric lymphoma in Brazil: a study of 203 cases - Jark, P. C. [UNESP]; Fracacio, C. P.; Anai, L. A. [UNESP]; Silva, M. C. L. [UNESP]; Calazans, S. G. [UNESP]; Senhorello, I. L. S. [UNESP]; Costa, M. T. [UNESP]; Sequeira, J. L. [UNESP]; Sueiro, F. A. R. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2020)
The immunophenotype is regarded as an independent prognostic factor in high-grade lymphomas, seeing that lymphomas of T-cell origin are associated with shorter survival time. Although a number of studies have evaluated the immunophenotypical profile of lymphoma in the USA and Europe, Brazilian research on the matter remains scarce. Exact characterization of the histopathological type is crucial to establish proper treatment and prognosis. This study evaluated the database of immunohistochemistry laboratories that perform immunophenotyping of canine lymphoma in Brazil. A total of 203 cases of multicentric lymphoma were classified according to the WHO classification. Immunophenotyping was able to identify 71.4% lymphomas of B-cell line, 27.1% of T-cell line and 1.5% of non-B cells and non-T cell lines. Diffuse large B-cell lymphoma was the most common with 59.1% of the cases. Among T-cell lymphomas, lymphoblastic was the most common (11.33% of the cases). Even though canine lymphomas tend to be high-grade, indolent lymphomas comprised 11.82% of the cases and T-zone lymphoma was the most prevalent (8.86%). The immunophenotype of multicentric lymphoma in Brazil is similar to those in other parts of the world, which suggests similar etiologic factors to the development of this disease.
Keywords: dog; lymphoma; immunophenotype